Pickford family at the old home - Pickford, Joel:::::::::
Pickford family at the old home on McKinley. L-R: Patricia Pickford (Rollin's sister), Glenna Pickford, Ruth Lingby Pickford (Rollin's mother), Rollin A. Pickford, Sr. (Rollin's father), Jeff Pickford, Jimmy Pickford